2023
DOI: 10.3389/fmats.2023.1108048
|View full text |Cite
|
Sign up to set email alerts
|

Sb-doped Tl8.67 Sn1.33-xSbx Te6 nanoparticles improve power factor and electronic charge transport

Abstract: Thallium telluride Tl8.67 Sn1.33-xSbxTe6 nano compound doped with different concentration ratios of Sb (x = 0.63, 0.65, 0.66, 0.68, 0.70, or 0.72) was prepared using solid-state techniques, and the compound was heated up to 550 K in vacuum silica tubes. The structure of the nano system was studied using XRD and EDX. It was confirmed that, without any other impurities, the nano system had a single-phase tetragonal crystal structure. The measured Seebeck coefficient (S) of all nano compounds showed that S increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…For the system described in Eqs. ( 5 ) to ( 8 ), the following giving entropy generation relations are created to maximize heat transmission and reduce energy losses 1 , 2 , 13 . …”
Section: Description Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…For the system described in Eqs. ( 5 ) to ( 8 ), the following giving entropy generation relations are created to maximize heat transmission and reduce energy losses 1 , 2 , 13 . …”
Section: Description Of the Problemmentioning
confidence: 99%
“…Many researchers devoted special attention on exploring the nanofluids properties. Khan et al 1 discussed the exclusive features of nanofluids which report enhancement in the power systems and elctrinc charge systems. Ali et al 2 reported iron zinc nanoparticles via spectroscopic approach.…”
Section: Introductionmentioning
confidence: 99%